Demographic variables as measures of biological adaptation : a case study of postneolithic populations - Piontek, Janusz (Array, 1990)
The aim of this work is to try to show that the demographic description of a population does not convey a complete account of the biological structure of a group. Consequently, it must be analyzed in the light of the nature of the system, which determines the pattern of interaction. The author's purpose is to test the hypothesis that adaptive processes occurring in human populations are shaped by the structuring of relations between elements of the human system. Primary focus will be on results of studies of microevolutionary processes in postneolithic populations, paying particular attention to biocultural factors altering the intensity of natural selection at various stages of human development